Odpowiedzi

2010-03-26T19:41:25+01:00
A.c=ax-b
-ax=-c-b pomnożyc/<-1>
ax=c+b/a
x=c+b
5 2 5
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-26T19:52:21+01:00
A) ax-b=c; ax=b+c II:a; x=(b+c)/a
b) ax+bc=dx+e; ax=dx+e-bc II:a; x=(dx+e-bc)/a
c) ax-b/c=d; ax=d-b/c II:a; x=(d-b/c)/a
d) 2x-a/b-x=3; 2x-x=3+a/b; x=3+a/b
e) 2ax-b=2x+c; 2ax-2x=b+c; x(2a-2)=b+c II:((2a-2); x=(b+c)/(2a-2)
f) 2(a-x)-x=b(3-x); 2a-2x-x=3b-bx; -3x-bx=3b-2a; x(-3-b)=3b-2a; II:(-3-b);
x=(3b-2a)/(-3-b)
g) a+x/x=b; x/x=b-a; 1=b-a; (nie wyznaczono równ.spełn.dla każdej wart b=1+a
h) a/2-x=b/d; -x=b/d-a/2 II:(-1); x=-(b/d-a/2)
5 4 5
2010-03-26T20:04:17+01:00
A) ax-b=c ! ax=c+b ! x=c+b/a

b) ax+bc=dx+e ! ax=dx+e-bc ! x=dx+e-bc/a

c) ax-b/c=d ! ax=d-b/c ! x=d-b/ca

d) 2x-a/b-x=3 ! 2x-x=3+a/b ! x=3+a/b

e) 2ax-b=2x+c ! 2ax-2x=b+c ! x(2a-2)=b+c ! x=b+c/2a-2

f) 2(a-x)-x=b(3-x) ! 2a-2x-x=3b-bx ! -3x-bx=3b-2a ! x(-3-b)=3b-2a
x=3b-2a/-3-b

g) a+x/x=b ! x/x=b-a ! 1=b-a !

h) a/2-x=b/d ! -x=b/d-a/2 ! x=-(b/d-a/2)



2 5 2